Decreased Risk in the Pancreatic Cancer With History of Hay Fever: A Meta-Analysis - Wang, Guannan; Xu, Zhiwei; Zhu, Jie; Ren, Jiayu; Chen, Mina; He, Guijuan; Yu, Beibei (Frontiers in Public Health, 2020)
Background: An increasing incidence of pancreatic cancer has been observed worldwide over the last few decades. Previous reports suggested that hay fever, a common allergic disease, may function in pancreatic cancer. Data on hay fever as a risk or protective factor for pancreatic cancer was controversial in several case–control reports. So, we here did a meta-analysis on published studies to evaluate the association of hay fever and the risk of pancreatic cancer. Methods: A comprehensive literature search was performed through public databases. The association between hay fever and pancreatic cancer was evaluated by odds ratios (ORs) and 95% confidence intervals (CIs). The Cochran's Q test and I2 index were used to evaluate heterogeneity. Results: We included 8 population-based case–control studies involving 10,454 participants from 1986 to 2014. A history of hay fever was associated with a decreased risk of pancreatic cancer (OR, 0.57; 95% CI, 0.50–0.64, P < 0.00001) through fixed effect model. Conclusion: The result of our study suggested that hay fever may significantly decrease the risk of pancreatic cancer.